Delayed awakening from general anesthesia revealing Fahr syndrome: Case report and literature review. Issue 12 (22nd October 2020) - Mellagui, Yassine; Aabdi, Mohammed; Ouachaou, Jamal; Bkiyar, Houssam; Housni, Brahim
Abstract: Fahr syndrome (FS) is defined by the presence of bilateral and symmetrical intracerebral nonarteriosclerotic calcifications, localized in the central gray nuclei. We report the case of a patient who presented a postoperative delay in awakening and whose biological and radiological investigations revealed a FS. Abstract : We need to think about doing a brain scan in case there is any postoperative delay in waking up.